Determinants Influencing Household Waste Disposal Behavior in River Stream Areas - Ananda Dwiky; Ali Imron; Ketut Prasetyo; Dian Ayu Larasati (Universitas Muhammadiyah Ponorogo, 2026)
River pollution caused by household waste remains a serious environmental issue in many urban areas. This problem not only affects aquatic ecosystems but also poses threats to public health and the quality of life of surrounding communities. The urgency of this study lies in the need to understand the social and structural factors that influence household waste disposal behavior, so that environmental policies and intervention programs can be more effective and contextually relevant. Using a quantitative approach and multiple linear regression analysis, this study found that social norms have a significant influence on waste disposal behavior, as indicated by a regression coefficient of 0.746 and a significance value of 0.000 (p < 0.05). This means that collective awareness and informal social control play a crucial role in shaping environmentally responsible behavior. In contrast, the use of waste disposal facilities and existing policies showed no statistically significant influence. These findings highlight that behavioral change in environmental practices cannot rely solely on infrastructure and regulation, but must be supported by the strengthening of social values and active community participation. However, this study is limited by its reliance on cross-sectional data and the exclusion of other potential determinants such as economic conditions, educational background, and cultural factors that may also influence waste disposal behavior. Future research should incorporate longitudinal designs, qualitative approaches, and a broader range of variables to capture the complexity of household decision-making processes and provide more comprehensive insights for sustainable environmental management. Keywords: River; Population; Waste;